2007
DOI: 10.1111/j.1464-5491.2007.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of structured hospital‐based care compared with standard care for Type 2 diabetes—The Asker and Baerum Cardiovascular Diabetes Study, a randomized trial

Abstract: This study shows that 2 years of structured care combining lifestyle and pharmacological interventions improved several CV risk factors and reduced the estimated 10-year absolute risk for CHD in patients with Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…12 Conversely, increasing the focus on including the spouse might result in a spouse becoming overprotective, which might impact negatively on the patient's self-management of his or her diabetes. 22 The present study and a previous report highlight the need for providing patients and their families with appropriate, practical information about T2DM.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…12 Conversely, increasing the focus on including the spouse might result in a spouse becoming overprotective, which might impact negatively on the patient's self-management of his or her diabetes. 22 The present study and a previous report highlight the need for providing patients and their families with appropriate, practical information about T2DM.…”
Section: Discussionmentioning
confidence: 98%
“…13,14 Inclusion/exclusion criteria and recruitment procedures for this trial have been described previously. 9,12 …”
Section: Study Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals included in the prospective trial were referred for voluntary stress echocardiography and invasive coronary angiography. Details of the design and results of the cross-sectional and prospective studies have been published [7,11]. All participants gave written informed consent and the studies were conducted in accordance with the Helsinki Declaration and approved by the Regional Ethics Committee and the Norwegian Data Inspectorate.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, current understanding suggests that broad, multiple intervention strategies including lifestyle changes, aggressive blood pressure and lipid lowering, in addition to glucose control, are necessary for mitigating morbidity and mortality related to macrovascular disease [5,6]. Consistent with this concept, the prospective, randomized Asker and Bærum Cardiovascular Diabetes (ABCD) trial on 120 T2DM subjects found that structured care encompassing a comprehensive and intensive preventive strategy reduced the primary efficacy outcome of change in the estimated 10-year absolute risk for fatal coronary heart disease at 2 years compared to conventional care [7]. …”
Section: Introductionmentioning
confidence: 99%